Mare of Easttown [videorecording (DVD)] - Winslet, Kate; Nicholson, Julianne, 1971-; Smart, Jean; Rice, Angourie, 2001- (Warner Bros. Entertainment, 2021)
Academy Award-winner Kate Winslet plays Mare Sheehan, a small-town Pennsylvania detective who investigates a local murder as life crumbles around her. From creator and writer Brad Ingelsby, with all episodes directed by Craig Zobel, the seven-part limited series is an exploration into the dark side of a close community and an authentic examination of how family and past tragedies can define our present.